Андрей Блинов: о жизни и творчестве / А. Н. Власенко - Власенко Александр Никитич (Удмуртия, 1986)
Экземпляры: Армязьская библиотека (19860808) / Инвентарный номер: 18996 / Сис.шифр: 8Р2 / Авт.знак: В 58 / ГРНТИ: 17 / ББК: 83